2012
DOI: 10.1371/journal.pone.0033982
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Nitrogen Pollution and Assessment of Its Health Risks: A Case Study of a Typical Village in Rural-Urban Continuum, China

Abstract: Protecting groundwater from nitrogen contamination is an important public-health concern and a major national environmental issue in China. In this study, we monitored water quality in 29 wells from 2009 to 2010 in a village in Shanghai city, whick belong to typical rural-urban continuum in China. The total N and NO3-N exhibited seasonal changes, and there were large fluctuations in NH4-N in residential areas, but without significant seasonal patterns. NO2-N in the water was not stable, but was present at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 21 publications
(25 reference statements)
0
51
0
1
Order By: Relevance
“…Heavy metals, nitrites and organic pollutants in contaminated water and soil could increase the potential risk of cancers (Montesano and Hall, 2001;Hansen et al, 2003;Galiani et al, 2005;Wild et al, 2006;He, 2013). It is reported that contaminated water and food could even increase the morbidity and mortality of cancers, especially digestive cancers (Baudouin et al, 2002;Boffetta, 2006;Beaumont et al, 2008;El-Tawil, 2010;Gallagher et al, 2010;Ebenstein, 2012;Gao et al, 2012;Sun et al, 2014;Zhang et al, 2014;Zhao et al, 2014).…”
Section: Pollution Related Health Risks In Food Production Basesmentioning
confidence: 99%
“…Heavy metals, nitrites and organic pollutants in contaminated water and soil could increase the potential risk of cancers (Montesano and Hall, 2001;Hansen et al, 2003;Galiani et al, 2005;Wild et al, 2006;He, 2013). It is reported that contaminated water and food could even increase the morbidity and mortality of cancers, especially digestive cancers (Baudouin et al, 2002;Boffetta, 2006;Beaumont et al, 2008;El-Tawil, 2010;Gallagher et al, 2010;Ebenstein, 2012;Gao et al, 2012;Sun et al, 2014;Zhang et al, 2014;Zhao et al, 2014).…”
Section: Pollution Related Health Risks In Food Production Basesmentioning
confidence: 99%
“…As groundwater N mainly originates from soil leaching, high groundwater N concentration is often observed in areas dominated by agriculture (Di & Cameron, 2002;Gao et al, 2012). The Taihu Lake region (TLR) is one of the most intensive agricultural regions and the most economically developed areas in China (Zhu & Chen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The use of herbaceous legumes as green manure and as a source of elite biofertiliser strains for plant growth promotion can be regarded as sustainable agriculture. The use of inorganic fertilisers has been associated with greenhouse gas emission and pollution of underground water resources, particularly nitrate pollution (Gao et al, 2012). Polycultures using legumes are known to reduce pest population pressure on crops, thereby reducing the use of chemical pesticides (Amoako-Atta et al, 1983).…”
Section: Introductionmentioning
confidence: 99%